Hubungan Antara Frekuensi Dan Lama Penyemprotan Dan Interval Kontak Pestisida Dengan Aktivitas Cholinesterase Petani Di Desa Kembangkuning Kecamatan Cepogo - Zulmi, Nizar; , Heru Subaris Kasjono SKM., M.Kes; , Dwi Astuti SKM, M.Kes (2016)
Pesticides are one of the substances that are highly neurotoxic. Pesticide poisoning to the body in the form of declined in cholinesterase activity in the blood. Cholinesterase examinated can be done by checking blood cholinesterase activity. The aims of this study was to determine the relationship between frequency of spraying, spraying duration and interval of contact pesticides with blood cholinesterase activity on farmers in the Banjarejo sub-district Kembangkuning Cepogo. This researched using cross sectional study design with a number of respondents as many as 37 farmers. Variables studied include blood cholinesterase activity of respondents, frequency of spraying, spraying long time, and an interval of contact pesticides. The research located in the village of Kembangkuning, District Cepogo, Boyolali. The statistical test used was Spearman Rank. Based on the results of bivariate the study, showed that the variables which provide results is: The frequency of spraying (p-value 0.042; rs 0.287), spraying duration (p-value 0.000; rs 0.600), and an interval of contact pesticides (p-value 0.043; rs 0,285 ). The conclusion of this research is a factor long enough pesticide spraying and interval of contact pesticides has linked strong with the incidence of blood cholinesterase activity declining farmer in the Banjarejo village of Kembangkuning Cepogo District of Boyolali.